Indikatoren für eine nachhaltige Entwicklung: Eckpunkte eines Indikatorensystems für räumliche Planungsfragen auf kommunaler Ebene - Birkmann, Jörn (Raumforschung und Raumordnung | Spatial Research and Planning, 1999)
The paradigm of sustainable development, which since 1998 has been enshrined in the Federal Regional Planning Act (the Raumordnungsgesetz), has not so far been implemented to anything approaching a satisfactory degree. This is particularly true within local authorities, which were named explicitly in Agenda 21 as major agents of implementation. One important approach toward continuous monitoring of the implementation of a concept of development aimed at achieving sustainability is considered to lie in the use of indicators, which are currently a subject of discussion at all levels of spatial planning. The present contribution develops building blocks for a system of local indicators of sustainability. A case study on implementation of the indicator system provides the basis for outlining the problems and shortcomings associated with current information and data systems at local-authority level.
Keywords: Article